17β-Estradiol Is Involved in the Sexual Dimorphism of the Immune Response to Malaria - Cervantes-Candelas, Luis Antonio; Aguilar-Castro, Jesús; Buendía-González, Fidel Orlando; Fernández-Rivera, Omar; Nolasco-Pérez, Teresita de Jesús; López-Padilla, Monserrat Sofía; Chavira-Ramírez, David Roberto; Legorreta-Herrera, Martha (Frontiers in Endocrinology, 2021)
Malaria is the leading cause of parasitic infection-related death globally. Additionally, malaria-associated mortality is higher in men than in women, and this sexual dimorphism reflects differences in innate and adaptive immune responses that are influenced by sex hormones. Normally, females develop more robust immune responses against parasites than males. However, most clinical and laboratory studies related to the immune response to malaria do not consider sex as a variable, and relatively few studies have compared the sex-dependent role of 17β-oestradiol in this process. In this study, we decreased in vivo the levels of 17β-oestradiol by gonadectomy or administered 17β-oestradiol to intact or gonadectomised male and female CBA/Ca mice infected with Plasmodium berghei ANKA. Subsequently, we assessed the effects of 17β-oestradiol on parasite load; the percentages of different immune cells in the spleen; the plasma levels of antibodies and pro- and anti-inflammatory cytokines; and the mRNA expression levels of cytokine-encoding genes in the brain. The results showed that the administration of 17β-oestradiol increased parasitaemia and decreased body weight in intact female mice. Moreover, intact females exhibited higher levels of CD8+ T cells and lower levels of NK1.1+ cells than their male counterparts under the same condition. Gonadectomy increased IFN-γ and decreased TNF-α concentrations only in intact female mice, while 17β-oestradiol administration restored the levels of these cytokines. IL-10 levels were higher in intact females than in their male counterparts. Finally, the mRNA expression levels of cytokines coding genes in the brain showed a dimorphic pattern, i.e., gonadectomy upregulated Tnf, Il1b, and Il10 expression in males but not in females. Our findings explain the sexual dimorphism in the immune response to malaria, at least in part, and suggest potential sex-dependent implications for the efficacy of vaccines or drugs targeting malaria.